ANALYSIS OF INFLECTIONAL AND DERIVATIONAL IN THE LEGEND OF MOUNT TANGKUBAN PERAHU - Ramadhanty, Desti; Santoso, Iman (PROJECT (Professional Journal of English Education), 2024)
Morphology is the study of forms/word formation or the study of word structure. According to Todd cited in (Kusumawardhani, 2018) Morphology is the learning about of morphemes, morphology is the smallest unit of word or grammar. Affixation is a morphological process, where there is an affix attached to the root of a word. Affixes are divided into two namely prefix and suffix. Prefix is the addition of letters or several letters in front of the base word to form a new word and new meaning. Suffix is a letter or several letters added at the end of the word or root. Inflectional is a morphological process by adding an affix (suffix) to a word to change its form according to grammatical rules without changing the word class or the part of speech. Derivational affixes is a morphological process by adding both prefixes and suffixes by changing the part of speech or meaning to the words or morpheme base. The purpose research was to analyze the inflectional process and derivational process contained in the narrative text entitled The Legend of Mount Tangkuban Perahu. The research used a qualitative descriptive method. The researchers found there were 55 inflectional process and derivational process in the text. There are 41 of inflectional and 14 of derivational.